Partial least squares structural equation modeling using SmartPLS: a software review - Sarstedt, Marko; Cheah, Jun Hwa (Springer, 2019)
In their effort to better understand consumer behavior, marketing researchers often analyze relationships between latent variables, measured by sets of observed variables. Partial least squares structural equation modeling (PLS-SEM) has become a popular tool for analyzing such relationships. Particularly the availability of SmartPLS, a comprehensive software program with an intuitive graphical user interface, helped popularize the method. We review the latest version of SmartPLS and discuss its various features. Our aim is to offer researchers with concrete guidance regarding their choice of a PLS-SEM software that fits their analytical needs.